CMOS Circuits for Biological Sensing and Processing - Mitra, Srinjoy; Cumming, David R. S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book provides the most comprehensive and consistent survey of the field of IC design for Biological Sensing and Processing.  The authors describe a multitude of applications that require custom CMOS IC design and highlight the techniques in analog and mixed-signal circuit design that potentially can cross boundaries and benefit the very wide community of bio-medical engineers. Provides a single-source reference to the state-of-the-art in analog and mixed-signal circuit design for biological and chemical sensing; Highlights numerous applications, categorized as Ex-vivo, In-vivo, and Wearable and Technology Trends; Explains basic details of the circuits used in a very consistent manner, identifying clearly the CMOS and non-CMOS technologies used, along with the method to interact with the transducer (various kinds of electrodes, ion-sensitive layers, Carbon nanotubes etc.).
CMOS nano-pore technology -- Metabolomics on CMOS Personalised Medicine -- Flexible Single-Photon Image Sensors -- Photonic interaction with the nervous system -- Microelectronics for muscle fatigue monitoring through surface EMG -- IC Design for high-density Neural probe -- Implantable Microsystems for Personalised Anti-Cancer Therapy -- Compressed Sensing for Neural Recording compression and analysis -- Design optimization for wearable EEG sensors -- CMOS multimodal sensor array for biomedical sensing -- Micro-NMR on CMOS for biomolecular sensing -- Circuits and Systems for Biosensing with Microultrasound -- Very Large scale neuromorphic systems for biological signal processing -- Index.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronic Circuits and Systems; Processor Architectures